THE SURVIVAL, THE SUSTAINABILITY, AND THE NEW MEDIA DISRUPTION: A CASE STUDY OF THE NEWSPAPER INDUSTRY HARIAN FAJAR IN MAKASSAR CITY - Erniwati (KAREBA : Jurnal Ilmu Komunikasi, 2021)
The era of disruption is a period that requires the newspaper/print media industry to innovate and be creative to keep up with the times and technology. The tight competition in the newspaper industry requires media companies to be able to survive in the face of competitors. This article aims to analyze the sustainability resistance used by the Harian Fajar newspaper industry in Makassar City, so that it still exists in a very tight media competition. The method used in this research is a qualitative-exploratory approach with a case study approach, to answer how the sustainability of Harian Fajar newspaper in Makassar City is doing. The results of the study show that the application of divergence by Harian Fajar newspaper in Makassar City is to respond to changes in the way audiences read newspapers which were previously conventional, but now the public can enjoy digital content online. In addition, innovation and creativity efforts towards news and entertainment content as well as the application of media divergence are strategies used by Harian Fajar newspaper in Makassar City to stay afloat. This divergence concept is applied as an effort to make Harian Fajar effective in disseminating information by utilizing digitalized media such as the Fajar Online.co.id Portal and E-Paper to get closer to the readers. This was done by Harian Fajar newspaper in Makassar City as an effort to maintain its existence.